2022
DOI: 10.1101/2022.02.02.478854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constitutively active STING causes neuroinflammation and degeneration of dopaminergic neurons in mice

Abstract: The innate immune system can protect against certain aspects of neurodegenerative diseases, but also contribute to disease progression. Stimulator of interferon genes (STING) is activated after detection of cytoplasmic dsDNA by cGAS (cyclic GMP-AMP synthase) as part of the defense against viral pathogens, activating type I interferon and NF-kB/inflammasome signaling. In order to specifically test the relevance of this pathway for the degeneration of dopaminergic neurons in Parkinson's disease, we studied a mou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Szegö and coworkers corroborated this finding in a recent preprint where they showed that chronic activation of STING causes degeneration of dopaminergic neurons. Constitutively, active variant STING knock-in mice demonstrated the accumulation of pathological α-synuclein ( 154 ). STING activation may contribute to neurodegeneration in patients with a rare α-synucleinopathy, multiple-system atrophy ( 155 ).…”
Section: Smocs Inducing the Release Of Neurotoxic Inflammatory Mediatorsmentioning
confidence: 99%
“…Szegö and coworkers corroborated this finding in a recent preprint where they showed that chronic activation of STING causes degeneration of dopaminergic neurons. Constitutively, active variant STING knock-in mice demonstrated the accumulation of pathological α-synuclein ( 154 ). STING activation may contribute to neurodegeneration in patients with a rare α-synucleinopathy, multiple-system atrophy ( 155 ).…”
Section: Smocs Inducing the Release Of Neurotoxic Inflammatory Mediatorsmentioning
confidence: 99%